Evaluation of antihyperglycemic activity of aqueous stem bark extract of Boswellia dalzielii in alloxan-induced diabetic Wistar rats - Ahmad Alhassan Ibrahim; Muhammed Sani Abdussalami; Joseph Appah; Abdullahi Hussein Umar; Amina Umar Muhammad; Sani Haruna; Aminu Alhassan Ibrahim (Future Journal of Pharmaceutical Sciences, 2023)
Abstract Background Diabetes mellitus is one of the leading causes of morbidity and mortality globally. Although synthetic hypoglycemic agents are commonly used to manage this disorder, such medications, besides being unable to cure the disease, are expensive and associated with side effects. Conversely, medicinal plants have emerged as effective, safe and affordable alternative treatments. Boswellia dalzielii plant has been reported to possess ethnomedicinal properties for the treatment of various health conditions; however, scientific studies exploring this plant as antihyperglycemic agent are still limited. Thus, this study evaluated the antihyperglycemic activity of aqueous stem bark extract (ASBE) of B. dalzielii in alloxan-induced diabetic Wistar albino rats. Methods Phytochemical screening of the ASBE of B. dalzielii was conducted. Twenty male Wistar albino rats weighing 100–150 g divided into 4 groups (A–D) of five rats were used for the study. Group A served as the normal control and received neither ASBE of B. dalzielii nor glibenclamide. The treatment for the other three groups was as follows: Group B, 10 mg/kg of glibenclamide (diabetic control); Group C, 500 mg/kg ASBE of B. dalzielii; and Group D, 1000 mg/kg ASBE of B. dalzielii. Treatments were administered orally every 24 h for a period of 2 weeks. Blood glucose level and body weight were evaluated at weeks 0, 1 and 2. Histomorphological features of the rats’ pancreas in all the groups were compared. Results The phytochemical analysis revealed the presence of alkaloids, saponins, tannins, cardiac glycosides, flavonoids, carbohydrates, steroids and triterpenes. The two different doses of the plant extract significantly reduced blood glucose level at weeks 1 and 2 (all p < 0.05), with the 1000 mg/kg dose demonstrating a greater reduction compared with glibenclamide at week 2 (p = 0.014). However, only the 500 mg/kg dose led to restoration, albeit slight, of the pancreatic islet cells. Conclusion This study suggests that B. dalzielii plant exhibits a potent antihyperglycemic activity evidenced by reduced blood glucose levels and slight restoration of pancreatic islet cells. This plant could be, therefore, considered in the treatment of diabetes mellitus. Graphical Abstract